Black artists shaping the world - Jackson, Sharna (Thames & Hudson, 2021)
Written by award-winning Black children’s author Sharna Jackson, this engaging book introduces young readers to twenty-six contemporary artists from Africa and of the African diaspora, working in everything from painting, sculpture, and drawing to ceramics, installation art, and sound art. These include prominent American artists Kerry James Marshall, Faith Ringgold, portraitist to Michelle Obama Amy Sherald, and Kehinde Wiley; British Turner Prize-winning painters Lubaina Himid and Chris Ofili; renowned South African visual activist and photographer Zanele Muholi; Nigerian sound artist Emeka Ogboh; Sudanese painter Kamala Ibrahim Ishaq; Kenyan-British ceramicist Magdalene Odundo; Afrofuturist-inspired performance artist Harold Offeh; and moving image artist Larry Achiampong, among others. Sharna Jackson’s experience as an award-winning children’s author combined with the curatorial expertise of Dr. Zoeé Whitley, co-curator of the groundbreaking exhibition "Soul of a Nation: Art in the Age of Black Power," make this an essential introduction to Black artists working today. This volume will serve as revelation to a new generation of aspiring young artists